A Concept of Talent: Aspect of a School Librarian - Urška Repinc; Polona Vilar (Knjižnica, 2012)
ABSTRACT The article deals with different concepts of giftedness around the world and with appropriate pedagogical approach to gifted pupils. Gifted pupils are treated as pupils with special educational needs. There are many definitions of giftedness. It is agreed that it is a combination of intellectual abilities and creativity. It is important to recognize a gifted child. There are different pedagogical approaches to gifted children around the world. All pedagogical staff including school librarians is responsible for adequate service provision for gifted pupils.